Knowledge of Formal and Informal Regulations Affecting Wild Plant Foraging Practices in Urban Spaces in South Africa. Issue 12 (2nd December 2021) - Garekae, Hesekia; Shackleton, Charlie M.
Abstract: Although foraging wild plants is commonly perceived to be synonymous with rural areas, it is now increasingly recognized in urban areas. Notwithstanding, the regulations conditioning access to and rights to foraging in urban green spaces have seldom been examined. This study explored the formal and informal regulations governing access to and defining rights to forageable plant resources in the towns of Potchefstroom and Thabazimbi, South Africa. A random sample of 374 households was considered for the survey, complemented by in-depth interviews with 26 participants. Foraging occurred in a variety of public and private spaces, with the frequency of access differing with the type of space. The majority of the respondents were unaware of formal and informal regulations governing access to and use of urban landscapes. Recognizing foraging activities in urban landscapes is a fundamental step toward fostering active community involvement in the management and production of urban green spaces.